Tracing concepts - semantic network analysis as a heuristic device for classification - Elwert, Frederik (Classification from antiquity to modern times, 2017)
Since the digital age is affecting more and more aspects of historical studies, the need to explore and evaluate new computational methods for the constantly growing amount of digital resources has become greater than ever. Due to the huge amount of digitized text, new methods may help to answer innovative research questions, challenge existing theoretical patterns and generate new approaches and perceptions. The research field emerging as a result of these reflections, the so-called digital humanities, might increasingly be incorporated into the established humanities disciplines. The authors present in this paper a heuristic method for the study of textual sources that allows the tracing of ancient Egyptian concepts and classification schemes by uncovering the relationships of words. By using automated network analysis in combination with a close reading of the sources, we can trace the outlines of the semantic field of a word; the ancient Egyptian expression for day serves as an example and will be studied in detail with this method.